2019
DOI: 10.1002/ca.23509
|View full text |Cite
|
Sign up to set email alerts
|

Published Human Cadaveric Measurements Are Strongly Biased Toward the Elderly Population

Abstract: Understanding of anatomy is based on the study of anatomical variations. Morphometric variations can have important implications in surgical practice. The sizes of some anatomical structures are affected by age; however, cadavers used in anatomical research are usually of advanced age. The main aim of this study is to quantify the mean age of samples in cadaveric studies reporting morphometric values. PubMed was searched for the last 3 years to locate cadaveric studies reporting size values, excluding histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the present study, it was not possible to detect the early onset of pterion sutural obliteration because the minimum age of our donors was 40 years old with an average of 65.5 years old. It was previously noted that anatomical features are affected by age, and the published anatomical findings are heavily biased towards the elderly population [24]. Our findings also showed that sutural obliteration of the pterion was only observed in males.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, it was not possible to detect the early onset of pterion sutural obliteration because the minimum age of our donors was 40 years old with an average of 65.5 years old. It was previously noted that anatomical features are affected by age, and the published anatomical findings are heavily biased towards the elderly population [24]. Our findings also showed that sutural obliteration of the pterion was only observed in males.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, many cadavers are expectedly of the elderly, and it is obvious between anatomists and clinicians. In literature, several morphometric measurements reported are obtained from certain ages, but this is in line with the global life expectancy and consequently with the physiological and pathophysiological changes that it induces, improving the knowledge of the medical doctors ( 36 ); they will act above all on this age in daily practice.…”
Section: Methodsmentioning
confidence: 96%
“…Weak effect of age was found on the annulus rigidity since most of the experiments are done on cadavers of mature or quasi-mature discs that have an almost stable stress-strain conduct. This observation was reported by Yammine [65] who mentioned that experimental results available in the literature that were established on human cadaveric are biased toward elderly. Also, we can see from the stress-strain curves in Fig.…”
Section: Correlation Between Intrinsic Mechanics Of Disc and Its Func...mentioning
confidence: 73%